Inhibiting HSP90 changes the expression pattern of PINK1 and BNIP3 and induces oxidative stress in colon cancer cells - Ejlal Abu-El-Rub (5168183) (2025)
Background Cancer cells can modulate the expression of many proteins that are essential for supporting their uncontrolled proliferation. Heat shock protein 90 (HSP90) is ubiquitously expressed in most cell types and participates in controlling many survival pathways. Cancer cells utilize HSP90 in order to prolong their survival, thus they tend to overexpress it. Based on its importance for cancer cells, we aim to investigate the molecular mechanisms that link HSP90 inhibition in colon cancer cells with oxidative stress and mitochondrial stress—related regulators. Materials and methods We used RKO colon cancer cells, blocking HSP90 with the inhibitor AT13387 and HSP90 siRNA. Cell proliferation and apoptosis were measured via CCK8 ELISA and Fluorescent Apoptosis Assays. Western blotting and immunocytochemistry assessed oxidative and mitochondrial stress markers BNIP3, PINK1, GP91/NOX2, and IRE1α in treated cells. Results Our findings reveal that inhibiting HSP90 with AT13387 reduces RKO cell viability by suppressing proliferation and enhancing Annexin-V expression, indicative of increased apoptosis. This rise in apoptosis is associated with PINK1 downregulation and BNIP3 upregulation, markers of mitochondrial dysfunction and oxidative stress, respectively. Additionally, AT13387 treatment elevated the protein level of GP91, a marker of oxidative stress, and IRE1α, a marker of ER stress. Similarly, genetic knockdown of HSP90 in RKO cells produced comparable effects, including reduced cell survival and a decreased PINK1/BNIP3 ratio. Conclusion Targeting HSP90 in colon cancer cells disrupts their survival by decreasing PINK1 and increasing BNIP3, which activates oxidative and endoplasmic reticulum stress, ultimately triggering apoptosis. Other Information Published in: Molecular Biology Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11033-025-10303-x